Grammatical Semantic Aspect Analysis of the Lyrics of Songs in the Album Menari dengan Bayangan by Hindia - Vianie, Daniella Cristie; Sardjono, Sardjono; Rahmayantis, Marista Dwi (CV. Srikandi Kreatif Nusantara in collaboration with Institut Teknologi Mojosari Nganjuk, 2025)
This study aims to examine and describe the grammatical semantic aspects found in the lyrics of the album Menari dengan Bayangan by Hindia, focusing on four main elements: reference, substitution, ellipsis, and conjunction. The research employs a descriptive qualitative method with a grammatical semantics approach. Data were collected through documentation and observation of song lyrics, and analyzed using the Miles and Huberman data analysis model. The findings indicate that exophoric personal reference is the most dominant form, reflecting the emotional relationships among the lyrical subjects. Substitution is utilized as a stylistic strategy to replace nouns or phrases, while ellipsis appears in both nominal and clausal forms to convey implicit meaning efficiently. Conjunctions are used in various types causal, adversative, sequential, and additive to maintain cohesion and coherence across the lyrics. This study demonstrates that Hindia's lyrics function not only as a medium for emotional expression but also as a complex linguistic structure. The implications include expanding the application of grammatical semantics in popular literary texts and strengthening interdisciplinary approaches in language and cultural studies.